PENGARUH KUALITAS LAYANAN PENGIRIMAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PENGGUNA LAYANAN EKSPEDISI SHOPEE EXPRESS) - Dirgantini, Devi; Sarwoto (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This study aims to evaluate the impact of delivery service quality (order condition, information quality, and personal contact quality) on customer loyalty. The research focuses on users of Shopee Express delivery services in West Java. The convenience sampling technique was used in this study. A total of 99 respondents participated in the survey through online questionnaires. The collected data were analyzed using structural equation modeling (SEM) with partial least squares (PLS) method. The results indicate that delivery service quality (information quality and personal contact quality) has a positive impact on customer loyalty. However, order condition does not have a positive impact on customer loyalty. This research provides important insights for stakeholders to improve delivery service quality in the future.